Does the Experience of Imprisonment Affect Optimism About Reentry? - Cid, José (The prison journal, 2021)
Desistance research has linked prison inmate expectations with positive outcomes after release, but very little research addresses what makes them optimistic about their future. Using data from a representative sample, this article analyzes whether the manner in which a prison sentence is served impacts expectations about reentry. Results show that experiencing harsh prison conditions makes incarcerees more pessimistic about reentry, while receiving family support during imprisonment has the opposite effect. Given that the mission of the prison system is to prepare prisoners for a successful reentry, this study has several implications for correctional agencies.